Nedd4-2 Haploinsufficiency in Mice Impairs the Ubiquitination of Rer1 and Increases the Susceptibility to Endoplasmic Reticulum Stress and Seizures - Liu, Xiaoliang; Zhang, Lu; Zhang, Hebo; Liang, Xiaoyan; Zhang, Bijun; Tu, Jianqiao; Zhao, Yanyan (Frontiers in Molecular Neuroscience, 2022)
Neural precursor cell expressed developmentally downregulated gene 4-like (NEDD4-2) is an epilepsy-associated gene encoding an E3 ligase that ubiquitinates neuroactive substrates. An involvement of NEDD4-2 in endoplasmic reticulum (ER) stress has been recently found with mechanisms needing further investigations. Herein, Nedd4-2+/− mice were found intolerant to thapsigargin (Tg) to develop ER stress in the brain. Pretreatment of Tg aggravated the pentylenetetrazole (PTZ)-induced seizures. Retention in endoplasmic reticulum 1 (Rer1), an ER retrieval receptor, was upregulated through impaired ubiquitination in Nedd4-2+/− mouse brain. Nedd4-2 interacted with Rer1 more strongly in mice with Tg administration. The negative regulation and NEDD4-2-mediated ubiquitination on RER1 were evaluated in cultured neurocytes and gliacytes by NEDD4-2 knockdown and overexpression. NEDD4-2 interacted with RER1 at higher levels in the cells with Tg treatment. Disruption of the 36STPY39 motif of RER1 attenuated the interaction with NEDD4-2, and the ubiquitinated RER1 underwent proteasomal degradation. Furthermore, the interactome of Rer1 was screened by immunoprecipitation-mass spectrometry in PTZ-induced mouse hippocampus, showing multiple potential ER retrieval cargoes that mediate neuroexcitability. The α1 subunit of the GABAA receptor was validated to interact with Rer1 and retain in ER more heavily in Nedd4-2+/− mouse brain by Endo-H digestion. In conclusion, Nedd4-2 deficiency in mice showed impaired ubiquitination of Rer1 and increased ER stress and seizures. These data indicate a protective effect of NEDD4-2 in ER stress and seizures possibly via RER1. We also provided potential ER retention cargoes of Rer1 awaiting further investigation.